Perbandingan Produktivitas dan Biaya Bongkar Overburden pada Excavator PC2000 Bucket Standart dengan Modifikasi pada Pertambangan Batubara: Studi Kasus PT. Putra Perkasa Abadi Job Site Bukit Asam - Setiawan Nur Wahid; Nancy Oktyajati; Sri Purwati; Aland Dewa Yasa (IAI Nasional Laa Roiba Bogor, 2024)
A company requires productivity to achieve predetermined goals. Productivity is an important aspect for a company in determining its future business because productivity is the effective and efficient use of resources to produce or increase the output of goods or services. PT. Putra Perkasa Abadi is targeting overburden productivity on its PC2000 excavator to be 820bcm/hour, but the company wants to increase or increase production by modifying the PC2000 excavator from the standard size of only 12m³ to 14m³ without changing other components in order to get better results. more without increasing operational costs and costs for removing soil layers. The modified tool is PC2000 with hull number EX2045 bucket 14m³ by comparing the standard tool PC2000 with hull number EX2044 bucket 12m³, the picking test was carried out on 16 December 2023 shift 1. The EX2045 data results obtained a productivity of 914bcm with operational costs of 18.270.000 and costs for removing soil layers of 2,176 /bcm while EX2044's productivity is 823bcm with operational costs of 18.210.000 with a land demolition price of 2,418/bcm, so EX2045 is 11% more efficient than EX2044 and provides productivity of 11.4% of the company's target provided that it must minimize obstacles in the field that hinder the production process so that production can run optimally as expected.